Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.
Publisher: Société québécoise de recherche en musique

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

'The digital is everywhere': Negotiating the aesthetics of digital mediation in Montreal's electroacoustic and sound art scenes - Valiquet, Patrick Joseph (Université d'Oxford, 2014)
In this thesis I argue that the relationship between the increasing ubiquity of digital audio technologies and the transformation of aesthetic hierarchies in electroacoustic and sound art traditions is not deterministic, but negotiated by producers and policy-makers in specific historical and cultural contexts. Interviews, observations, and historical data were gathered during sixteen months of ethnographic fieldwork in the Canadian city of Montreal between 2011 and 2012. Research was conducted and analysed in collaboration with a transnational group of researchers on a programme of comparative research that tracked global changes to music and musical practice associated with digital technologies. The introduction presents Montreal as a rich ecology in which to track struggles for aesthetic authority, detailing its history as a key site of electroacoustic and sound art production, and its local positioning as a politically strategic 'hub' for the Canadian culture industry. Core chapters examine the specific role of digital mediation in the negotiation of electroacoustic and sound art aesthetics from multiple interlocking perspectives: the recursive relationship between technological affordances and theories of mediation; the mobilisation of digital technologies in the delineation of cultural, professional and generational territories; the political contestation of digital literacies and pedagogies; the articulation of the digital's opposition with analogue in the construction of instruments and recording formats; and the effects of the digital on the dynamics of genre and genre hierarchies. The concluding chapter offers a critique of the notion that digital mediation has shifted the balance between the normative and the generative dimensions of genrefication in the scenes in question, and closes by suggesting how a better understanding of this shift at an empirical level can inform an ongoing rethinking of the interaction between technology and aesthetics among scholars, policy makers, and musicians.

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme « réactivateur » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception